Beyond the Folds: Emergent Properties in Paper - Rhodes-Pruitt, John (East Carolina University, 2023)
In this body of work I explore the relationship between visual art, information science, and the geometry of paper in an attempt to create a unique visual language with which I make records; not unlike writing in a journal. Using cyanotype, origami, drawing, and digital techniques I co-opt the language of computers (binary) to represent aspects of myself in paper form, blending the analog and digital into a distinctive way of communicating. The work is informed by my understanding of Constructor Theory, Information Theory, and Quantum Mechanics with which I draw thematic comparisons between the fundamental nature of who I am with the fundamental nature of the universe.
Keywords: Printmaking; Photography; Alt-process; Blueprint; Post-postmodernism; Constructor Theory; Geometry in art; Computer art; Paper art; Information science--Art; Cyanotypes; Origami